Uric acid and uric acid/creatinine ratio are associated with GDM in women undergoing IVF/ICSI - Liu, Yvonne; Hocher, Johann-Georg; Ma, Shujuan; Hu, Liang; Chen, Huijun; Zhang, Xiaoli; Gong, Fei; Krämer, Bernhard K.; Lin, Ge; Hocher, Berthold (Frontiers in Endocrinology, 2025)
IntroductionWith ongoing global lifestyle changes and economic development, the prevalence of hyperuricemia has steadily increased. Elevated levels of serum uric acid (SUA) have been linked to gestational diabetes mellitus (GDM); however, this relationship has not yet been specifically evaluated in women undergoing assisted reproductive technology (ART). Therefore, this study aimed to analyze the relationship between pre-pregnancy SUA as well as SUA to serum creatinine (SCr) ratio and GDM in women undergoing ART.MethodsThis retrospective cohort study was carried out at the Reproductive and Genetic Hospital of CITIC-Xiangya in Changsha, Hunan, China, and included 1027 women who underwent their first ART treatment between 2017 and 2018. SUA levels were measured during the baseline visit prior to any ART procedures, and GDM incidence was recorded based on screening results from the oral glucose tolerance test.ResultsGDM was diagnosed in 172 (16.7%) of the 1027 patients. When comparing SUA quintiles, significant differences were observed in GDM incidence, and several other parameters (including pre-pregnancy weight, BMI, blood glucose, blood pressure, SCr, lipid parameters, anti-Müllarian Hormone, follicle stimulating hormone, and testosterone). SUA was independently associated with GDM incidence after adjusting for potential confounding factors in multivariate analysis (OR 1.004, p = 0.003). Moreover, the SUA/SCr ratio displayed an even stronger association (OR 1.226, p = 0.003).ConclusionPre-pregnancy SUA levels – and particularly the SUA/SCr ratio – were significantly associated with GDM among women undergoing ART.